Treatment of Zenker’s diverticulum using a novel grasping-type scissors forceps allows fast, safe, and effective endoscopic diverticulotomy - Rath, Timo; Siebler, Jürgen; Neurath, Markus F.; Nägel, Andreas (Endoscopy International Open, 2018)
Background and study aims Although several endoscopic techniques have been described for Zenker’s diverticulotomy, no standardized endoscopic approach has been established in clinical routine to date. This study aimed to assess the efficacy and safety of endoscopic diverticulotomy using the Clutch Cutter.Patients and methods Cricopharyngeal myotomy was performed in six prospectively enrolled patients with symptomatic Zenker’s diverticulum, using the Clutch Cutter. Procedural details such as duration, complications, and technical success were recorded and compared to the outcomes of 15 patients who received needle-knife-based myotomy.Results Myotomy with the Clutch Cutter was feasible in all six patients with complete diverticulotomy in a single session in all patients. Mean procedure time of the Clutch Cutter myotomy was 19 minutes without major complications. During follow-up, one patient had diverticulum recurrence after 10 months, which was successfully re-treated. Mean procedure time with the needle-knife was 43 minutes and a mean of 2.7 myotomy sessions was required for complete diverticulotomy.Conclusion Endoscopic diverticulotomy using the Clutch Cutter is safe, effective, and fast. Larger studies comparing myotomy using the Clutch Cutter with other endoscopic techniques are highly warranted.